1995
DOI: 10.1088/0268-1242/10/11/004
|View full text |Cite
|
Sign up to set email alerts
|

Calculated structural and electronic properties of boron phosphide under pressure

Abstract: The structural and electronic properties of the zinc-blende, p-Sn and rock-salt phases of BP are calculated within the local-density approximation. Two competing methods-LMTO and the pseudopotential plane-wave method-have been used. The agreement between the two electronic structure methods is excellent. We obtain the pressure versus volume equation of state and the pressure dependence of the structural and electronic parameters in good agreement with experiment and some previous calculations. Our calculations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 22 publications
6
14
1
Order By: Relevance
“…Besides, it is very close to the ones calculated within LDA [16,18,25,26,29] and PBE-GGA [21]. In the present work, the indirect gap of BP ( v 15 → min ) ( Table 3) is the closest one to the measured values among the other results calculated within LDA [16,18,40,42,44] and GGA [21,43,45] except the ones corrected in GW method [29] and the use of proper lattice constant of BP [27]. The other band energies of BP calculated in the present work 15 ) are all comparable to the measured ones (Table 3).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Besides, it is very close to the ones calculated within LDA [16,18,25,26,29] and PBE-GGA [21]. In the present work, the indirect gap of BP ( v 15 → min ) ( Table 3) is the closest one to the measured values among the other results calculated within LDA [16,18,40,42,44] and GGA [21,43,45] except the ones corrected in GW method [29] and the use of proper lattice constant of BP [27]. The other band energies of BP calculated in the present work 15 ) are all comparable to the measured ones (Table 3).…”
Section: Resultssupporting
confidence: 87%
“…It was reported that, the calculated lattice constant of c-BP is becoming very close to its experimental value when both LDA and GGA's are utilized in total energy minimization calculations [27,43,45]. The bulk modulus of c-BP calculated by the first principles methods given above [27,16,18,[40][41][42]44,45,43] are in the narrow range of 160-176 GPa. The cohesive energy of c-BP is overestimated (11.45 eV/atom-pair) in DFT calculations utilizing LDA scheme [44].…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…Under hydrostatic pressure the lowpressure phase is destabilized and a structural phase transition to a high coordination phase appears. For AlP the phase transition occurs in the range of 14-17 GPa, for GaP the transition from the cubic to high-pressure phase appears in the range of 20 GPa, for InP the transition pressure is in the range of 10 GPa [1], and finally for BP the transformation comes into view in the range of 150 GPa [2].…”
Section: Introductionmentioning
confidence: 99%